From response to transformation: how countries can strengthen national pandemic preparedness and response systems. (28th November 2021) - Haldane, Victoria; Jung, Anne-Sophie; Neill, Rachel; Singh, Sudhvir; Wu, Shishi; Jamieson, Margaret; Verma, Monica; Tan, Melisa; De Foo, Chuan; Abdalla, Salma M; Shrestha, Pami; Chua, Alvin Qijia; et al.
Abstract : Victoria Haldane and colleagues delve into the characteristics of national responses to covid-19. They suggest actionable steps at a national level that can guide states to achieve the independent panel's recommendations for making this the last pandemic